Truth, conceptual schemes, and the world (Diametros, 2005)
In the article I criticize the conception according to which the conceptual character of human cognition falsifies the theory of truth understood as a kind of correspondence between the truth-bearer and the truth-maker. Arguing against the conceptions of Josef Mitterer, Donald Davidson, Richard Rorty and Andrzej Szahaj, I defend the claim that the conceptual character of human cognition is irrelevant to the critique of correspondence theories of truth. I justify this claim by using the example of Nicolas Rescher’s conception of conceptual idealism, which is similar to Hilary Putnam's internal realism but does not rule out truth as a kind of correspondence.